Assessment of Heavy Metal Contamination of Groundwater in Rural Areas of Duhok City, Iraq - Salim, Sarmad; Mohammed, Rangeen Shihab; Kareem, Idrees Majeed (Engineering, Technology & Applied Science Research, 2024)
This study investigates the quality of groundwater sources in the rural areas of Duhok City, Iraq, with a particular focus on heavy metal contamination, chemical composition, and properties of water. Water samples from 14 wells, serving as the main water source for the surrounding areas, were collected and analyzed. Water quality parameters including calcium (Ca²⁺), magnesium (Mg²⁺), chloride (Cl⁻), potassium (K⁺), and sulfate (SO₄²⁻) values ranged from 24 to 105.6 mg/L, 6.832 to 50.752 mg/L, 18 to 34 mg/L, 1 to 7 mg/L, and 3.4 to 38 mg/L respectively. Common heavy metals like manganese (Mn), lead (Pb), copper (Cu), and cobalt (Co) exhibited varying concentrations. Most parameters meet the WHO standards, except for the elevated potassium in one sample, requiring attention. Additionally, 50% of the sampled wells showed elevated cadmium (Cd) levels. Possible sources of contamination include industrial activities, agricultural runoff, and geological factors, highlighting the importance of ongoing monitoring and targeted interventions to ensure access to clean and safe water.